Validation of rhodamin b analysis method in beef sausage with visible spectrophotometry instruments - Kurniaty, Santyas; Salamah, Nina (Universitas Ahmad Dahlan, 2023)
Sausage is made from meat that has been chopped and then mashed, seasoned, and put in a symmetrical elliptical sleeve, made either from animal intestines or artificial wrapping (casing). To attract consumer interest, synthetic food coloring such as Rhodamin B is added. Rhodamin B is a dye prohibited from being used in products, according to the Director General of POM No. 00386/C/SK/II/1990, because the use of Rhodamin B for a long time can cause liver damage and cause cancer. The purpose of this study was to validate the analytical method of rhodamine B in beef sausages by visible spectrophotometry. The sample used in this study was a beef sausage with a reddish-pink characteristic and without a brand. The validation parameters of the method used in this study are linearity, precision, LOD, LOQ, and accuracy. The data obtained were then analyzed using the SPSS Kolmogorov-Smirnov method, then ANOVA was used. The validation results of linearity test methods, LOD LOQ, precision, and accuracy met the requirements of PPOP GMP in 2013.